Alan Sokal - Follari, Roberto (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2000)
The affaire Sokal proves to have important effects in the social sciences. Nevertheless, the same effects must be properly understood in what can be inferred and what cannot. Among the later, finishing epistemological problems in the social sciences. The essay reviews Sokal's arguments and proposes a critical reading in order to understand his scope.